Development of Flash Card Learning Media at 3D Distance Materials - Fitri Umardiyah; Ade Ilud Nabila (LPPM Universitas KH. A. Wahab Hasbullah, 2022)
ABSTRACT This study aims to develop and produce flash card learning media that has a fairly good level of validity and practicality in three-dimensional material at the high school level. This type of research is RnD (Research and Development) with the ADDIE development model which includes 5 stages, namely Analysis, Design, Development, Implementation, Evaluation. The subject of this research is MA Al - Azhar students as many as 19 students. The instruments used in this study were interview guides to teachers, material validation as well as media by Mathematics Education Lecturers and Mathematics Teachers, student response questionnaires and card playing results tests. The results showed that: (1) The results of material and media validation obtained a percentage of 94% (very feasible) by Mathematics Lecturers and 87% by Mathematics Teachers and (2) The results of the practicality of the media at the time of the test reached a percentage of 85.53% (very good). Keywords: Flash Card Learning Media, Types of RnD Research, ADDIE Development Model, Three Dimensions.